MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA PAMIJAHAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Azizah Mursyidah; Gilang Permana Putra (SAHID DEVELOPMENT JOURNAL, 2022)
Pamijahan Village is a village located in Pamijahan District, Bogor Regency, West Java Province. Pamijahan Village has sufficient natural resources to develop and prosper socially and economically in the community. In community service, access to sharia financing is programmed for Micro, Small and Medium Enterprises (MSMEs) in Pamijahan Village, Pamijahan District, Bogor Regency. This community service activity was preceded by identifying problems with MSME actors, then collecting data. Then process the data and information, and after that a solution plan is prepared. The solution plan is to provide training to increase the knowledge and understanding of MSMEs in sharia financing, and increase MSME insight and trust.